The assessment of how businesses that offer accounting services might include time–driven activity–based costing - Kristina Rudžionienė; Rūta Klimaitienė; Ieva Gerulaitytė (Икономика и компютърни науки, 2025)
The evaluation of the Time-Driven Activity-Based Costing (TDABC) model for accounting service providers explores the origins of modern cost accounting models, their calculation methodologies, and their respective strengths and limitations. Drawing on theoretical insights, the study applies the TDABC model in a real-world setting within an accounting firm that manages financial records for nineteen companies. The findings offer a comprehensive perspective on the model’s potential benefits and challenges in practical application. The analysis underscores its effectiveness in refining cost allocation processes and optimizing resource utilization. Furthermore, the study identifies key obstacles to implementation and provides strategic recommendations for maximizing the model’s efficiency in accounting firms.